The long fall [large type] - Mosley, Walter (Mosley, Walter. Leonid McGill mysteries., 2009)
Leonid McGill, a New York City private detective, tries to put his past life behind him. But it's not that easy when someone like Tony "The Suit" Towers expects you to do a job; when an Albany P.I. hires you to track down four men known only by their youthful street names; and when your 16-year-old son, Twill, is getting in over his head with a suicidal girl.